Da Symbol Dat Under da Stuffs: Teaching the Language of Maths to Aboriginal Learners of Standard Australian English as a Second Dialect. Issue 1 (August 2019) - Watts, Janet; Gardner, Rod; Mushin, Ilana
Abstract : Failure to adequately address language differences between home and school is one of the many ways in which education systems frequently disadvantage Aboriginal students. Children from predominantly Aboriginal English-speaking homes face specific challenges, as the language differences between their home variety and the Standard Australian English (SAE) of the curriculum and classroom are often rendered 'invisible', with little explicit accommodation to the fact that such children are essentially immersed into the SAE classroom (e.g. Dixon, 2013 ; McIntosh, O'Hanlon, & Angelo, 2012 ; Sellwood & Angelo, 2013 ). One consequence of this invisibility is that it has been very hard to see during classroom time, where these language differences appear to affect children's engagement with the curriculum. In this paper, we present a micro-analysis of a year 2 maths lesson in a class of Aboriginal learners of SAE as an additional language/dialect, where children are being taught to use location words (e.g. under, above ) as mathematical language. We have examined the precise ways in which the children's home variety and SAE were used in this lesson, and where differences between these two varieties appeared to impact their understanding of the concepts being taught. We differentiate between the kinds of classroom language that provide a challenge to learners of SAE and the kinds that do not.